Economic evaluation of photovoltaic and energy storage technologies for future domestic energy systems – A case study of the UK. (15th July 2020) - Wang, Yue; Das, Ridoy; Putrus, Ghanim; Kotter, Richard
Abstract: Developments in photovoltaic (PV) technologies and mass production have resulted in continuous reduction of PV systems cost. However, concerns remain about the financial feasibility for investments in PV systems, which is facing a global shrinking of government support. This work evaluates the investment attractiveness of rooftop PV installations and the impact of energy storage systems (ESS), using the UK as a case study. The evaluation considers the location of installation, the temporal evolution of the supporting policies, local energy consumption, electricity price and cost of investment at different years. Furthermore, the use of electric vehicles (EVs) as an alternative to ESS for complementing PV systems is also investigated. Optimisation techniques are employed to schedule ESS and EV energy exchange in order to maximise the investment return. The results show that the net present value of PV systems in the UK has dropped from £28, 650 in 2011 to £1, 200 in 2017, due to declining government support towards PV technologies. It further shows that by incorporating ESS with PV systems, the benefit in 2017 can be increased by 46%. Conversely, employing the EV as energy storage would not bring additional benefits, considering the associated battery degradation and the current battery manufacturing cost. Highlights: Dynamic economic evaluation considering spatiotemporal impact, policy and tariffs. Verification of investment plan against the UK's PV deployment data. Use of stationary and mobile storage to increase PV return on investment. Optimal sizing of PV/storage systems based on real-life data.